Herramienta computacional modular a partir del modelo dinámico de un aerogenerador de eje horizontal con características mecánicas, eléctricas y electrónicas. (2022)
Nowadays the power generation from renewable sources, is a national interest topic. Nevertheless, the wind power generation at a residential level has not beed promoted in our contry yet, even though regulation of instalation and commercialization for small generators already exist. Part of the problem, is teaching to the community about this generation system, which should be support with computational tools taht facilitate understanding of these technologies. Commercially, there are some software applications that explore these technologies [1][2][3]. Nevertheless, the software that is in web pages for analysis and teaching of wind power generation systems usually has a license or is developed for a higher level than a Mechatronic program. Therefore, a software tool is presented in this TIG, which is conformed of a graphical interface and a simulation of a horizontal axis generator, which has beed modeled using computational tools that consider mechanical, electrical and electronic characteristics. The paper presents different configurations that an aerogenerator can have. Showing key information to make the computational tool. Also the geometric modeling of each piece is included, using Solidworks software, in which assembly mode was used to couple all pieces in a 3D figure, and so get the physical parameters of each piece. With the system parameters the mathematic model of horizontal axis generator was obtained, using Euler Lagrange equations. Two equations in total were realized to describe the system and later a block diagram was built in Simulink to validate its behaviour numerically. After “aerogenerator” system construction in Simulink, the graphical interface was made. Finally, the tool validation was realized.